Evaluation of the electroflotation efficiency for the oil-containing shipping waters treatment - Vozniuk, Marta; Shabliy, Tetiana (Vìsnik Nacìonalʹnogo tehnìčnogo unìversitetu Ukraïni <<Kiïvsʹkij polìtehnìčnij ìnstitut ìmenì Ìgorâ Sìkorsʹkogo>>. Serìâ <<Hìmìčna ìnženerìâ, ekologìâ ta resursozberežennâ>>, 2023)
The article describes the problems of formation and purification of ship oil-containing waters. The effectiveness of electroflotation using aluminum and iron anodes for the extraction of oil from water-oil emulsions with different mineralization was assessed. Electroflotation treatment of water-oil solutions provides 98.6–99.9 % oil removal using aluminum or iron electrodes at an anodic current density of 1.65–7.39 A/dm2 for highly mineralized waters and 0.07–0.50 A/dm2 for fresh water. Water treatment during the first 15 minutes provides a sharp decrease in oil content from 100 mg/dm3 to 1.31–2.52 mg/dm3, almost regardless of the type of anode metal. The efficiency of oil extraction from water mainly depends on its mineralization. In mineralized (salty) water, the treatment process is more efficient. In fresh waters, aluminum anode provides higher water purification efficiency compared to iron anode. However, in the case of pre-treatment of the iron anode with an alkali solution with the formation of a magnetite layer on it, this anode is characterized by the highest purification efficiency for low-salt waters, providing a degree of water purification at the level of 99.9 %.